An Economical High‐Throughput "FP‐Tag" Assay for Screening Glycosyltransferase Inhibitors. (21st January 2021) - Yin, Xinjian; Li, Jiaxin; Chen, Senhua; Wu, Yuping; She, Zhigang; Liu, Lan; Wang, Yue; Gao, Zhizeng
Abstract: O ‐GlcNAc transferase (OGT) is involved in many cellular processes, and selective OGT inhibitors are valuable tools to investigate O‐GlcNAcylation functions, and could potentially lead to therapeutics. However, high‐throughput OGT assays that are suitable for large‐scale HTS and can identify inhibitors targeting both acceptor, donor sites, and allosteric binding‐sites are still lacking. Here, we report the development of a high‐throughput "FP‐Tag" OGT assay with bovine serum albumin (BSA) as a low‐cost and superior "FP‐Tag". With this assay, 2‐methyleurotinone was identified as a low‐micromolar OGT inhibitor. This type of assay with BSA as "FP‐Tag" would find more applications with other glycosyltransferases. Abstract : High performance, low cost : A wash‐free, low‐cost fluorescent‐polarization‐based high‐throughput assay has been developed for O ‐GlcNAc transferase. Such an assay is "catalytic", thus only needing minimal amounts of enzymes and could potentially identify inhibitors targeting both the acceptor and donor binding‐sites.